ANALYSIS OF THE RESULTS OF USING AMINO, AMIDE AND NITRILE SORBENTS IN HYDROPHILIC INTERACTION LIQUID CHROMATOGRAPHY - A. S. Osipov (Ведомости Научного центра экспертизы средств медицинского применения, 2018)
The article summarises the results of studies of hydrophilic  interaction  liquid chromatography performed  from 2013 until 2017. The analysis of results obtained  during separation  of a number  of model mixtures of compounds  having different nature  helped to compare  the characteristics  of columns  packed with amino,  amide and nitrile sorbents. It was demonstrated that columns packed with amino sorbents could be used for the analysis of both hydrophilic compounds  and some hydrophobic compounds  containing acidic (4-hydroxybenzoic acid) and potentially acidic groups (nitro groups of nitro compounds;  phenolic hydroxyl groups of butylhydroxyanisole isomers and parabens). It was discovered that chromatographic columns packed with nitrile and amide sorbents have common properties and can be used for the analysis of hydrophilic compounds (hydroxycarbamide) and platinum coordination compounds, but cannot be used for the analysis of butylhydroxyanisole isomers, esters of p-hydroxybenzoic acid and nitrate  esters of isosorbide. The article offers hypotheses about possible mechanisms  of interaction  between test substances and sorbents. It was concluded  that the increase in the acetonitrile  content  in mobile phases, which increases the retention time of the test substances and results in better resolution between their peaks, illustrates the mechanism  of hydrophilic interaction  liquid chromatography.